CELIAC DISEASE SCREENING IN A LARGE DOWN SYNDROME COHORT: COMPARISON OF DIAGNOSTIC YIELD OF DIFFERENT SEROLOGICAL SCREENING TESTS - Dilek Uludağ Alkaya; Seçil Sözen; Birol Öztürk; Nuray Kepil; Tülay Erkan; Hüseyin Tufan Kutlu; Beyhan Tüysüz (İstanbul Tıp Fakültesi Dergisi)
Objective: Down syndrome (DS) patients have a higher risk of developing Celiac disease (CD) than the general population. This study aimed to estimate the prevalence of CD in DS patients and compare the diagnostic performance of the screening algorithms. Material and Method: A cohort of 1117 DS patients were included. Patients were grouped according to the initial screening method. Anti-gliadin antibody (AGA)-IgA/IgG were measured in the first, endomysial antibody-IgA (EMA) in the second, and tissue transglutaminase (tTG)-IgA/IgG in the third group. Additionally, EMA was also measured in patients with elevated tTGIgA or tTG-IgG levels. In the follow-up, 225 patients were rescreened. Intestinal biopsy was planned in patients with positive AGA-IgA/IgG, positive EMA, or more than threefold elevated tTG-IgA levels. Result: Based on the initial screening, 34.5% of the patients in the first group underwent a biopsy, and 2.3% were diagnosed with CD. In the second and third groups, 1.8% and 1.6% of patients underwent biopsy, and CD was diagnosed in 0.5% and 1.3%, respectively. Among all patients, 1.3% were diagnosed with CD at initial screening. Two hundred twenty-five patients with negative initial screening tests or intestinal biopsy were rescreened; 8% underwent biopsy and CD was confirmed in 4.9%. Overall, 2.3% of patients were diagnosed with CD. The positive predictive value of AGA-IgA and AGA-IgG was low (13.6% and 7.2%, respectively) compared to EMA (69.6%) and tTG-IgA (66.7%). Gastrointestinal or extraintestinal symptoms were present in 42.3% of CD patients, and none of them had short stature. Conclusion: Celiac disease was detected in 2.3% of DS patients. The CD detection rate was 1.3% at initial screening but increased to 4.9% at rescreening. Our results strongly suggest that CD screening should be performed regularly in all DS patients, whether they are symptomatic or not.